2013
DOI: 10.5114/aoms.2012.30786
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research Effect of 1α-25-dihydroxyvitamin D 3 on intimal hyperplasia developing in vascular anastomoses: a rabbit model

Abstract: IntroductionA common problem encountered in routine daily practice of cardiovascular surgery is migration of smooth muscle cells leading to intimal hyperplasia developing at vascular anastomosis sites which then causes luminal narrowing. The aim of this study was to investigate the antiproliferative effect of 1,25 (OH)2D3 on intimal hyperplasia.Material and methodsTwenty-one male white New Zealand rabbits weighing 2-3 kg were selected. There were 3 groups of animals each consisting of 7 rabbits. Group 1 was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…There were no statistically significant differences between the vehicle and paricalcitol arteries. However, trends in stenosis were observed that were generally aligned with data published in the literature [10,20]. Next, we explored potential mediators of tissue injury in intimal hyperplasia secondary to endothelial damage and the effect of paricalcitol.…”
Section: Paricalcitol Intimal Hyperplasia and Stenosis Secondary To E...supporting
confidence: 66%
See 3 more Smart Citations
“…There were no statistically significant differences between the vehicle and paricalcitol arteries. However, trends in stenosis were observed that were generally aligned with data published in the literature [10,20]. Next, we explored potential mediators of tissue injury in intimal hyperplasia secondary to endothelial damage and the effect of paricalcitol.…”
Section: Paricalcitol Intimal Hyperplasia and Stenosis Secondary To E...supporting
confidence: 66%
“…Vitamin D had previously been reported to protect from neointimal hyperplasia [10,11,20,21], although not by all authors [22]. However, the therapeutic use of vitamin D is marred by potential adverse effects on calcium-phosphate metabolism, as overdosing can cause hypercalcemia, hyperphosphatemia, hypercalciuria, urolithiasis, nephrocalcinosis and kidney failure [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An antiproliferative effect of 1α-25-dihydroxyvitamin D 3 on smooth muscle cells was recently studied. Hyperplasia developing in vascular anastomoses was significantly lowered [ 11 ]. That finding may be important because vitamin D 3 deficit is a common finding in hemodialysed patients.…”
Section: Discussionmentioning
confidence: 99%